2012
DOI: 10.1039/c2lc20751f
|View full text |Cite
|
Sign up to set email alerts
|

Progress toward multiplexed sample-to-result detection in low resource settings using microfluidic immunoassay cards

Abstract: In many low resource settings multiple diseases are endemic. There is a need for appropriate multi-analyte diagnostics capable of differentiating between diseases that cause similar clinical symptoms. The work presented here was part of a larger effort to develop a microfluidic point-of-care system, the DxBox, for sample-to-result differential diagnosis of infections that present with high rapid-onset fever. Here we describe a platform that detects disease-specific antigens and IgM antibodies. The disposable m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
65
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(65 citation statements)
references
References 29 publications
0
65
0
Order By: Relevance
“…The use of LPS as a serodiagnostic marker of salmonelloses is not new; several studies have reported its utility for detection of acute typhoid in serum and saliva. [19][20][21][22] However, uptake and wide clinical evaluation has been slow, possibly because of perceived problem with a lack of specificity. More detailed studies are underway in this laboratory to evaluate the issue of LPS specificity and cross-reactivity, and to evaluate the diagnostic properties of LPS from several different bacterial species to detect specifically the antibodies of the corresponding infection.…”
mentioning
confidence: 99%
“…The use of LPS as a serodiagnostic marker of salmonelloses is not new; several studies have reported its utility for detection of acute typhoid in serum and saliva. [19][20][21][22] However, uptake and wide clinical evaluation has been slow, possibly because of perceived problem with a lack of specificity. More detailed studies are underway in this laboratory to evaluate the issue of LPS specificity and cross-reactivity, and to evaluate the diagnostic properties of LPS from several different bacterial species to detect specifically the antibodies of the corresponding infection.…”
mentioning
confidence: 99%
“…Using pressure sensitive adhesive, different materials can be bonded to each other. An example is the multilayered microfluidic immunoassay card presented by Lafleur and coworkers (44). Proof of principle was provided with the detection of the IgM antibodies against Salmonella typhi LPS and malarial antigen HRPII from Plasmodium falciparum.…”
Section: Examples Of Diagnostic Assays In Microfluidicsmentioning
confidence: 99%
“…The existing sequential flow devices either introduce valving mechanisms into pumping systems, such as paper-based microfluidic circuits, 39,40 or build integrated micropumps based on the flow control structures, such as the Quake systems. 33 In our work, pneumatic diaphragm microvalves are integrated into an mlSIP device since both of the fluidic actuation and the diaphragm microvalves are built with multi-layer structures and driven by the vacuum pressure, 49 which is described as unified pumping and control.…”
Section: Automatic Microfluidic Sequential Handlingmentioning
confidence: 99%
“…Microfluidic sequential flow devices have been developed for bioassays, such as pneumatic microvalve-based systems, [30][31][32][33] capillary-based systems, [34][35][36][37][38][39][40] the SlipChip systems, [41][42][43] and manual valving systems. 44 For most of these systems, liquid pumping process and flow control functions are separately driven by different accessory equipment, which ultimately increases the system complexity and the overall cost.…”
Section: Introductionmentioning
confidence: 99%